Closed Gastroschisis - Mohammed Abdel-Latif; Mohamed Hisham Soliman; Khaled Mohaned El-Asmar; Mohamed Abdel-Sattar; Ibrahim M Abdelraheem; Ehab A El-shafei (EL-Med-Pub, 2017)
Closed gastroschisis is a rare entity usually associated with intestinal atresia and short bowel syndrome. We report two cases of closed gastroschisis presenting with neonatal intestinal obstruction and para-umbilical evisceration without an abdominal defect.